Improving Glucocorticoid Sensitivity of Brain-Homing CD4+ T Helper Cells by Steroid Hormone Crosstalk - Koetzier, Steven C.; van Langelaar, Jamie; Wierenga-Wolf, Annet F.; Melief, Marie-José; Pol, Kim; Musters, Suzanne; Lubberts, Erik; Dik, Willem A.; Smolders, Joost; van Luijn, Marvin M. (Frontiers in Immunology, 2022)
In early multiple sclerosis (MS), an IFN-γhighGM-CSFhighIL-17low CD4+ T-cell subset termed T helper 17.1 (Th17.1) reveals enhanced capacity to infiltrate the central nervous system. Th17.1 cells express high levels of multidrug resistance protein 1 (MDR1), which contributes to their poor glucocorticoid responsiveness. In this study, we explored whether glucocorticoid sensitivity of Th17.1 cells can generically be improved through synergy between steroid hormones, including calcitriol (1,25(OH)2D3), estradiol (E2) and progesterone (P4). We showed that human blood Th17.1 cells were less sensitive to 1,25(OH)2D3 than Th17 cells, as reflected by lower vitamin D receptor (VDR) levels and reduced modulation of MDR1, IFN-γ and GM-CSF expression after 1,25(OH)2D3 exposure. Upon T-cell activation, VDR levels were increased, but still lower in Th17.1 versus Th17 cells, which was accompanied by a 1,25(OH)2D3-mediated decline in MDR1 surface expression as well as secretion of IFN-γ and GM-CSF. In activated Th17.1 cells, 1,25(OH)2D3 amplified the suppressive effects of methylprednisolone (MP) on proliferation, MDR1 surface levels, secretion of IFN-γ and granzyme B, as well as expression of brain-homing markers CCR6 and VLA-4. The addition of P4 to 1,25(OH)2D3 further enhanced MP-mediated reduction in proliferation, CD25, CCR6 and CXCR3. Overall, this study indicates that glucocorticoid sensitivity of Th17.1 cells can be enhanced by treatment with 1,25(OH)2D3 and further improved with P4. Our observations implicate steroid hormone crosstalk as a therapeutic avenue in Th17.1-associated inflammatory disease including MS.